“Theater Departments” in the Funds of Siberian Libraries in the Pre-revolutionary Period - Ju. V. Timofeeva (Библиосфера, 2024)
The relevance of the topic is due to the wide possibilities of using library funds not only for education and upbringing of an individual, but also for organizing and conducting leisure activities, there providing plays from the fund for amateur performances and special literature to help stage. In some libraries, special theater departments were formed to facilitate the search for such literature. Their study is one of the areas of book culture transformation research in social communications of the 19th – 21st centuries. The purpose of this article is to present the results of identification and analysis of “theater departments” in Siberian libraries of the pre-revolutionary period. This study is based on viewing more than two hundred catalogs of Siberian libraries of the 19th – early 20th centuries, which made it possible to identify six of them that had independent theater departments in the pre-revolutionary period. The results are as follows. Six libraries had such departments. Most of them – 4 out of 6 – were city public libraries. For the first time, the quantitative indicators of the theater departments were calculated: the number of titles of books and volumes in them, their place among other departments according to these two criteria. Most of the titles and volumes were in the theater departments of Barnaul and Nerchinsk city public libraries, less than the rest – in Kurgan. The funds of the theater departments contained mainly dramatic works by Russian and foreign authors. The works by domestic playwrights prevailed. The plays by the famous Russian playwright A. N. Ostrovsky were widely presented in these departments. Theatrical periodicals written out by Siberian libraries are listed, among which the magazines “Artist” and “Theater and Art” are the most common. The main areas of interaction between libraries and organizers of amateur performances have been identified, which can be mutually beneficial to modern cultural institutions.